Implementation of Ki Hajar Dewantara's Leadership in Improving Teacher Discipline at SDN 2 Nanggeleng. - Lina Ningrum; Ujang Cepi Barlian; Siti Nurhasanah; Shofaryanty Nurhayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study discusses the application of Ki Hajar Dewantara's leadership concept which can improve a teacher's discipline. The background of this research is based on problems that often arise from the disciplinary attitude of a teacher, namely there are still many teachers who come late to school, teachers have not optimized learning hours, and assignments are not done optimally. Therefore, the role of a leader here is very necessary in providing firmness, motivation, and policies to teachers who are less disciplined in carrying out their duties. This research was conducted at SDN 2 Nanggeleng using a descriptive qualitative approach and the research methods used were interviews, observation, and documentation study. The results of the study describe that Ki Hajar Dewantara's leadership concepts, namely Ing-Ngarso sungtulodo, Ingmadya Mangunkarso, Tutwuri Handayani, serve as guidelines for the principal in leading SDN 2 Nanggeleng. The evaluation program carried out by the school principal in improving teacher discipline in peer assessment. It can be concluded that the application of Ki Hajar Dewantara's leadership concept can improve teacher discipline at SDN 2 Nanggeleng. Besides this success, consideration is needed to provide rewards and punishments for teachers who commit disciplinary violations, and for teachers who obey discipline. Which will then be applied to become motivation in improving teacher discipline.